Integrasi Pembelajaran Kolaboratif untuk Penguatan Keterampilan Berpikir Kritis dalam Pendidikan IPA - Mukminah, Mukminah; Hirlan, Hirlan (CV. Global Cendekia Inti, 2025)
Mastery of critical thinking skills is one of the primary demands of 21st-century education, including in science subjects, which emphasize scientific processes and evidence-based problem solving. However, classroom practices in schools often remain focused on rote memorization of concepts, limiting students' opportunities to develop higher-order thinking skills. This article aims to theoretically examine the relationship between collaborative learning models and the development of critical thinking skills within the context of science education. The review was conducted through a literature analysis of various relevant studies and theoretical frameworks. The analysis reveals that collaborative learning—which emphasizes social interaction, idea exchange, and the collective construction of knowledge—significantly contributes to the development of students’ critical thinking abilities. Models such as Problem-Based Learning, Discovery Learning, Guided Inquiry, and Jigsaw have been shown to encourage students to pose questions, construct arguments, evaluate information, and draw logical conclusions. The integration of additional strategies, such as the use of mind mapping and digital technologies, further enhances the effectiveness of collaboration in improving the quality of science learning. Therefore, collaborative learning can be positioned as a strategic pedagogical approach for enhancing students’ critical thinking skills. This article recommends the systematic implementation of collaborative models in science education, supported by technology integration and strengthened teacher competencies, in order to foster a generation that is critical, reflective, and adaptive to the challenges of the 21st century.